Comparison of Higher-Order Aberrations After Single-Step Transepithelial and Conventional Alcohol-Assisted Photorefractive Keratectomy - Kemal Özülken; Çağrı İlhan (Türk Oftalmoloji Dergisi, 2020)

(untitled)
Objectives:To compare the asphericity and higher-order aberration (HOA) outcomes of single-step transepithelial photorefractive keratectomy (tPRK) and conventional alcohol-assisted PRK (aaPRK) in patients with myopia and myopic astigmatism.Materials and Methods:Of the 108 eyes of 54 patients enrolled in the study, tPRK was performed on 54 (50%) eyes and aaPRK was performed on 54 (50%) eyes. The following parameters were compared: corrected distance visual acuity (CDVA), spherical equivalent (SE), flat and steep keratometry, intraocular pressure, central corneal thickness, asphericity, and HOAs including horizontal and vertical coma, horizontal and vertical trefoil, spherical aberration, second-order vertical coma, and aberration coefficient.Results:The demographic and baseline characteristics were similar between the two groups (p>0.05, for all). The aberration coefficient value was significantly lower in patients treated with aaPRK compared to patients treated with tPRK at postoperative 3 months, 6 months, and 1 year (p=0.022, p=0.019, and p=0.017, respectively). Differences in the other variables were statistically insignificant (p>0.05 for all).Conclusion:Both tPRK and aaPRK procedures obtain similar postoperative CDVA, SE, asphericity, and HOA outcomes, except the aberration coefficient value.